Strategi Peningkatan Kinerja UMKM melalui “UMKM Naik Kelas” Pada UMKM di Kecamatan Cempaka Putih Jakarta Pusa - Sutandi Sutandi; Resista Vikaliana; Yusup Rachmat Hidayat; Yuli Evitha (Institut Ilmu Sosial dan Manajemen Stiami, 2020)
n Indonesia, SMEs have a strategic role and a very large contribution to the national economy by contributing 53.3% of total GDP (Gross Domestic Product). The number of SMEs in Indonesia reaches around 56.2 million units and is capable of absorbing 97.2% of the total workforce. Based on data from the Central Statistics Agency (BPS) the growth of online-based trading business has increased in the last 10 years, to 26 million or up 17% and followed by the number of SMEs reaching more than 55 million units, but many challenges must be faced by SMEs in facing MEA. The form of community service activity training is titled: